FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MEROKOK PADA MAHASISWA PSDKU UNPAD PANGANDARAN - Siti Azzahra, Rahma; Koswara, Iwan; Fuady, Ikhsan (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2025)
This study aims to analyze the factors that affect smoking behavior in PSDKU students of Padjadjaran University Pangandaran. A quantitative approach was used by involving 102 student respondents who were selected based on certain characteristics. The variables studied included individual factors (stress and self-esteem), family factors (relationships with parents and economic conditions), and environmental factors (peer influence and social norms). The results of multiple regression analysis showed that environmental and individual factors had a significant influence on smoking behavior, while family factors did not have a significant influence. Environmental factors, such as peer influence and social norms, are the dominant predictors in students' smoking behavior. The conclusion of this study emphasizes the need for integrative efforts from campuses, families, and communities in overcoming smoking behavior through education, psychological support, and the formation of a smoke-free environment.